A Community-Based Approach to Supporting the Mental Health of Rural Youth - Ashlyn Michael; LaToya O'Neal; Erin Kersey; Angela Nielsen; Karen Coker; Larry Forthun (EDIS)
This publication highlights the role the established presence of UF/IFAS Extension in rural regions can play in the dissemination of community-based professionals into these areas. The integration of these professionals and the various programs and services they offer will serve as a buffer to the many stressors faced by rural residents, the complexities of which often lead to overall poor mental health. Written by Ashlyn Michael, LaToya O’Neal, Erin Kersey, Angela Nielsen, Karen Coker, and Larry Forthun, and published by the UF/IFAS Department of Family, Youth and Community Sciences, November 2022.